1959
DOI: 10.1152/jappl.1959.14.3.339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of posture on pulmonary dead space in man

Abstract: Physiologic dead space was determined in the supine and upright postures by simultaneous sampling and subsequent analysis of arterial blood and expired gas for Pco2. In seven normal men there was invariably a higher dead space in the upright than in the supine position. The difference averaged 83 ml and was statistically significant (S.E. 25 ml and P < 0.01). The ratio of dead space to tidal volume also invariably increased on assuming the upright posture. Evidence is presented for believing that most of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

1963
1963
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 0 publications
4
31
0
Order By: Relevance
“…They concluded that the regional differences in V/Q ratio were less in all subjects and positions than those found in upright man, indicating that V and Q are generally better matched in the other positions. This is in accordance with observations that the alveolar-arterial O 2 tension differences (A -a)O 2 were smaller in the supine than in upright position (Riley et al, 1959). Since the 1960s distribution of perfusion and ventilation has been explained by the effect of gravity on regional perfusion pressure and regional lung compliance (West and Dollery, 1960).…”
Section: Ventilation/perfusion Heterogeneitysupporting
confidence: 92%
“…They concluded that the regional differences in V/Q ratio were less in all subjects and positions than those found in upright man, indicating that V and Q are generally better matched in the other positions. This is in accordance with observations that the alveolar-arterial O 2 tension differences (A -a)O 2 were smaller in the supine than in upright position (Riley et al, 1959). Since the 1960s distribution of perfusion and ventilation has been explained by the effect of gravity on regional perfusion pressure and regional lung compliance (West and Dollery, 1960).…”
Section: Ventilation/perfusion Heterogeneitysupporting
confidence: 92%
“…Minute volume and tidal volume can also be divided into separate contributions from the alveoli and from the conducting airways or 'dead-space ': j-E = V~A + V~D j.VT = VA+ VD Normal dead space is about 150 ml and represents 20-30% of tidal volume at rest (Fowler, 1948;Riley, Permutt, Said, Godfrey, Cheng, Howell & Shephard, 1959). It increases only slightly during exercise, when it constitutes a smaller proportion of tidal volume (Jones, McHardy, Naimark & Campbell, 1966).…”
Section: Theoretical Problemsmentioning
confidence: 99%
“…When CL was determined during G-suit inflation, the subjects breathed into a recording spirometer so placed that they were able to observe their respiratory ex- (17,18). Arterial Pco2 and the Pco, of mixed expired gas were determined with a Pco2 electrode system.3 VD(phyS) was determined by the method of Riley and co-workers (19) in seated subjects before and 10 minutes after administration of atropine.…”
Section: Fig 1 Apparatus For Positive-pressure Breathingmentioning
confidence: 99%